DMF-T index and DMF-S score in 12-year-old children - Anggreini, Rima; Susilawati, Sri; Suryanti, Netty (Universitas Padjadjaran, 2014)
Introduction: Oral health status can be seen from caries index. Children are the most vulnerable population against dental caries. The age of 12 years old is one of the caries monitoring indicators (global monitoring age). The purpose of this study was to determine the DMF-T Index and DMF-S score of 12-year-old children at SDN Sayang and SDN Cibeusi, Jatinangor District. Methods: This research was a descriptive type. The technique used in taking the samples was total sampling method. The total samples in SDN Sayang were 52 samples and in SDN Cibeusi were 28 samples. Result: The results shows that the DMF-T Index of 12-year-old children in SDN Sayang is 2.75 and in SDN Cibeusi is 2.85. The DMF-S score in SDN Sayang are 262 cases, meanwhile the DMF-S score in SDN Cibeusi are 142 cases. Conclusion: Based on this research, it can be concluded that the DMF-T Index of 12-year-old children in SDN Sayang and SDN Cibeusi are moderate based on WHO criteria. The DMF-S score shows that the most affected surface of teeth is occlusal surface.